Zakat Management in Indonesia: A Qualitative Analysis using N-Vivo - Uula, Mimma Maripatul; Izza, Nadia Nurul (Management and Sustainability, 2023)
This study attempts to map research related to zakat management in Indonesia published by Scopus indexed journals from 2006 to 2023. NVivo 12 Plus was used to conduct thematic review and frequency was used to evaluate 145 publications in scientific literature. The results found that there is a fluctuating number of publications from year to year related to zakat management research in Indonesia which indicates that this topic is an interesting topic and should continue to be developed. In addition, various focuses of discussion and cluster analysis that describe the research path in zakat management research in Indonesia include Social Justice and Zakat Management in Indonesia, Social Finance and Zakat Management in Indonesia, Effective Zakat Management in Indonesia, and Financial Institutions and Zakat Management in Indonesia. This research can be used as a starting point for experts to build a graphic visualization of zakat management research patterns in Indonesia in published scientific research.